Hegemonic Past: Exclusion of Subaltern Histories in NCERT Textbooks. Issue 1 (June 2020) - Patil, Swarali
History textbooks are always a site of contestation. Therefore, present political struggles for maintaining hegemony or overthrowing it play on the site of history. History as discipline has always been dominated by androcentric values. Therefore, feminist historiography was emerged which not only criticized existing androcentric historiographies but suggested new ways to do history. This article tries to analyze inclusions and exclusions within history textbooks. In the first part of the article I will try to analyze why certain histories never became part of the textbook and what are the sources that are used to write history. In this article I will analyze VIII standard NCERT history textbooks in India (Central level Government textbooks) through caste and gender lenses. In 2005 the theme of NCERT History textbooks changed from 'our past' (singular) to 'our pasts' (plural). However, this change does not reflect in the content of the textbook. I am using content analysis as a method to analyze pictures and texts. I will also try to contextualize the text within time and space. The exclusion and inclusion of history in the textbooks depends on the contemporary caste, patriarchal hegemony in our society. The dominant mainstream history has become part of these textbooks, but subaltern history is excluded from it. In this article I will also talk about the Dalit histories, Dalit women histories and tribal histories which are silenced as 'other' and remained part of counterculture but did not become part of these mainstream textbooks. In the later part of the article, I will try to look in what way the histories are altered to fit in a particular framework especially the histories of subalterns. At the end I will focus on how textbooks always build the idea of hegemonic nation and nationalism in students mind. Therefore, through this article I will analyze the ways through which the 'other' is being silenced in history textbooks.